(untitled) (CIPEEX, 2022)
THE ACCESSIBILITY AND INCLUSION OF VISUALLY IMPAIRED INDIVIDUALS IN SOCIETY HAS YET TO EVOLVE AND IMPROVE GREATLY. SIMPLE SITUATIONS SUCH AS WALKING ON THE SIDEWALKS AND CROSSING A STREET ARE COMPLICATED FOR THESE CITIZENS, SINCE, IN ADDITION TO THE MAJORITY OF SIDEWALKS BEING BUMPY, UNEVEN AND LACKING TACTILE FLOORS, TRAFFIC LIGHTS ARE NOT ADAPTED TO EMIT, FOR EXAMPLE, BEEPS. IN DENTAL PREVENTION AND TREATMENT, IT IS NOT DIFFERENT, SINCE RESEARCH INDICATES THAT PEOPLE WITH VISUAL IMPAIRMENT HAVE POOR ORAL HEALTH, REACHING VERY HIGH CPO-D SCORES, SINCE ORAL HEALTH DEPENDS ON A SET OF BIOLOGICAL CONDITIONS AND PSYCHOLOGICAL. VISUAL DEFICIENCY, BE IT BLINDNESS OR LOW VISION, INTERFERES WITH THE KNOWLEDGE OF ONE’S OWN BODY AND THE INTERRELATIONSHIP BETWEEN THINGS AND PEOPLE, INFLUENCING, MAINLY, THE ACTIVITIES OF SELF-CARE AND MOBILITY. DESPITE THE SIGNIFICANT ADVANCES IN THE AREA OF €‹€‹HEALTH IN DENTAL CARE FOR PATIENTS WITH SPECIAL NEEDS, THIS CARE IS STILL VERY PRECARIOUS IN BRAZIL. THIS IS DUE TO REASONS SUCH AS: FEW SPECIALIZED CENTERS FOR THE CARE OF THESE PATIENTS; A LIMITED NUMBER OF QUALIFIED DENTAL SURGEONS TO DO THIS TYPE OF TREATMENT; THE LACK OF TECHNOLOGICAL TOOLS THAT MAY CONTRIBUTE TO THE ACCESS OF THE VISUALLY IMPAIRED TO CONCEPTS OF DENTISTRY THAT GO FAR BEYOND BRAILLE AND, MAINLY, THE LACK OF KNOWLEDGE, MOTIVATION AND INTEREST OF THE FAMILY IN RELATION TO THE ORAL HEALTH OF THESE INDIVIDUALS. THUS, A VIDEO WAS DEVELOPED WITH THE AIM OF SHOWING THAT THE VISUALLY IMPAIRED HAVE RIGHTS THAT MUST BE RESPECTED; THE LEGISLATION MUST BE COMPLIED WITH ADAPTED SPACES AND PHYSICAL STRUCTURES AND IT IS POSSIBLE TO CARRY OUT THE HUMANIZED DENTAL TREATMENT AND WITH TECHNICAL ASPECTS THAT FACILITATE A BETTER UNDERSTANDING AND CONTROL OF THE TREATMENT, AS WELL AS A GREATER PARTICIPATION OF THE FAMILY. &NBSP; KEYWORDS: VISUALLY IMPAIRED PERSONS. HEALTH SERVICES ACCESSIBILITY. DENTAL CARE.